Experimental evaluation of pulse electric current effect on residual stresses in composite-to-copper joints - Stepanov, G.V.; Babutskii, A.I.; Mameev, I.A.; Ferraris, M.; Casalegno, V.; Salvo, M. (Проблемы прочности, 2008)
Experimental method for evaluation of residual stress distribution in carbon fiber reinforced carbon composite jointed to copper is presented. Pulse electric current passed through composite-to-copper joint essentially reduces the level of residual stresses. Представлено експериментальну методику щодо оцінки розподілу залишко вих напружень у з’єднанні композита (вуглець, зміцнений вуглецевими волокнами) з міддю. Установлено, що імпульс електричного струму, що пропущений через з’єднання композит-мідь, суттєво зменшує рівень залиш кових напружень. Представлена экспериментальная методика оценки распределения остаточных напряжений в соединении композита (углерод, упрочненный углеродными волокнами) с медью. Установлено, что импульс электрического тока, пропущенный через соединение композит-медь, существенно снижает уровень остаточных напряжений.